Les fonds d’archives du Fonds patrimonial Heure Joyeuse de la médiathèque Françoise Sagan : une histoire « humaine » - Viviane Ezratty (Strenae, 2016)
The Fonds Patrimonial Heure Joyeuse offers a collection of 80,000 children’s books from the 16th century to present day. The context of its creation within the Heure Joyeuse, the first specialized library for children created in France in 1924, also led to the building of its archives, initially connected to the institution itself, then, thanks to donations, it became gradually more focused on children’s publishing.